Analisis Pengaruh Gaya Kepemimpinan, Motivasi Kerja, Disiplin Kerja, dan Lingkungan Kerja Terhadap Kinerja Karyawan Kantor Pusat PT. Sun Star Motor Solo - Wahyuningsih, Sapti; , Drs. Eko Sugiyanto, M.Si (2015)
This research aims to understand the influence of the style of leadership, motivation work , discipline of work and work environment to the performance of the central office employees of pt sun solo star motor .The total sample study 77 respondents .Sample collection method uses the technique convenience of sampling .A method of the quality of data on test the validity of using product moment while the pearson reliabilitasnya using cronbach alpha .The technique of analysis of data used to test hypotheses include an analysis of linear double .All the data obtained have met the test the assumption of classical namely a test of normality , test and test multikolinearitas heteroskedastisitas . The research concluded that leadership style variable significantly influence employee performance Head Office PT. Sun Motor Solo. Evidenced by tcount (2.991)> t table (1,991) and 0,004 significance value < = 0.05. Motivation significant effect on employee performance Central Office PT. Sun Motor Solo. Evidenced by tcount (2.166)> t table (1,991) and 0,034 significance value < = 0.05. Work discipline variables have a significant effect on the performance of employees of the Central Office PT. Sun Motor Solo. Evidenced by tcount (2.150)> t table (1991) and the significant value of 0.035 < = 0.05. Work environment variables significantly influence employee performance Central Office PT. Sun Motor Solo. Evidenced by tcount (2.285)> t table (1,991) and 0,025 significance value < = 0.05.